Gambaran Potensi Interaksi Obat Amlodipin pada Pasien Hipertensi di Instalasi Rawat Jalan Puskesmas Mlati I Sleman Yogyakarta - Fatlah Furqon Kholik; Mardiana Puji Lestari; Sugiyono Sugiyono; Lutfi Hidiyaningtyas (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2026)
Background: Hypertension is one of the chronic diseases with high prevalence which is the main cause of death. One of the first lines of hypertension treatment is amlodipine. Amlodipine can be given as monotherapy, but if it is not effective in lowering blood pressure, then combination antihypertensive therapy can be given. The use of amlodipine together with various other drugs in hypertensive patients increases the risk of drug interactions that can affect the effectiveness of treatment. Research Objective: To determine the potential for drug interactions between amlodipine and other drugs in outpatients with hypertension at the Mlati I Sleman Health Center, Yogyakarta, January–December 2024. Research Methods: This study design was descriptive observational with a retrospective approach. A sample of 96 patients who met the inclusion criteria were taken using a purposive sampling technique. Data were collected from medical records and drug interactions were analyzed using Drugs.com. Data were analyzed univariately including patient characteristics, drug characteristics, and potential drug interactions. Research Results: The majority of patients were aged 56–65 years (29.17%), female (64.58%), and had comorbidities (83.33%). Amlodipine was mostly used in hypertensive patients alone (92.71%). The number of drugs used in this study was mostly <5 drugs (93.75%). From the evaluation results, 40 patients (41.67%) experienced potential drug interactions. Of the 47 drug interactions, the majority were moderate in severity (55.32%) with a pharmacodynamic drug interaction mechanism of 68%. Conclusion: There is a potential for amlodipine drug interactions in outpatient hypertensive patients, most of which are moderate with a pharmacodynamic mechanism.